Structural Characterization and Dynamics of a Layered 2D Perovskite [NH3(CH2)5NH3]MnCl4 Crystal near Phase Transition Temperature - Ae Ran Lim; Yeji Na (Crystals, 2022)
[NH3(CH2)5NH3]MnCl4 crystals are grown via slow evaporation, and the crystal undergoes a phase transition at 298 K (TC) according to differential scanning calorimetry, and the structures determined via X-ray diffraction at 173 and 333 K are orthorhombic systems in the space group Imma. These results differed slightly from those previously reported, and the reasons for this are analyzed. The thermal stability is relatively high, with a thermal decomposition temperature of approximately 570 K. The 1H spin-lattice relaxation times t1ρ exhibited very large variations, as indicated by the large thermal displacement around the 1H atoms, suggesting energy transfer at ~TC, even if no structural changes occurred. The influences of the chemical shifts of 1H of NH3 and short t1ρ of C1 adjacent to NH3 in cation are insignificant, indicating a minor change in the N−H⋯Cl hydrogen bond related to the coordination geometry of the MnCl6 octahedron. These properties will be make it a potential application for eco-friendly solar cells.